Deskripsi Penerapan Pembelajaran dengan Pendekatan Technological Pedagogical and Content Knowledge (TPaCK) di Kelas VI Sekolah Dasar Negeri 09 Pontianak Tenggara - Putri, Rahmaniar Islamiati; Kresnadi, Hery; Pranata, Rio (FONDATIA, 2023)
The purpose of this study was to describe the implementation of learning with the Technological Pedagogical and Content Knowledge (TPaCK) approach in class VI of Elementary School 09 Pontianak Tenggara. The method used in this research is descriptive qualitative research using observation guidelines, interview guidelines, and documentation. Qualitative data were obtained through observation sheets which included 4 aspects and 20 indicators, teacher interview guidelines consisting of 20 questions, and student interview guidelines consisting of 15 questions. The results of this study concluded that the implementation of learning with the Technological Pedagogical and Content Knowledge (TPaCK) approach was carried out by analyzing the interaction of learning models using the TPaCK approach. This approach involves aspects such as TK (Technological Knowledge), PK (Pedagogical Knowledge), CK (Content Knowledge), PCK (Pedagogical Content Knowledge), TPK (Technological Pedagogical Knowledge), TCK (Technological Content Knowledge), and TPaCK (Technological Knowledge). Pedagogical and Content Knowledge). Obstacles in implementing this approach involve human resources, facilities, and facilities. Each learning information technology approach has components such as vision, goals, development, planning, necessary facilities, learning methods, and learning evaluation. Efforts to overcome this obstacle include internal coaching in schools, improving the quality of education, and involving teachers in various training activities and seminars. This aims to align the vision and understanding of teachers towards education and improve their abilities as professional educators.